Induction of the smectic A phase in liquid crystalline mixtures formulated using non-chiral compounds with positive and negative dielectric anisotropy. (3rd July 2022) - Tykarska, Marzena; Zieja, Paulina; Strzeżysz, Olga; Garbat, Katarzyna; Morawiak, Przemysław; Piecek, Wiktor; Kula, Przemysław
ABSTRACT: The induction of the SmA phase in mixtures of non-chiral nematic compounds with the positive and the negative dielectric anisotropy is presented which is obtained by different substitutions of fluorine atoms. One component is a three-ring tolane with polar group – OCF3 in position 4 and two fluorine atoms in positions 3 and 5 in the terminal phenyl ring. The other component is two ring tolane with two or four fluorine atoms in the lateral position. Based on phase diagrams, the influence of the alkyl chain length of both types of compounds on the induction phenomenon is shown. Results of the X-ray measurements confirm that the induced phase is a monolayer SmA phase. The increase of the alkyl chain length causes the increase in the strength of the induction in mixtures, i.e. the induced SmA phase is observed for a wider range of the temperature and concentration of mixture components.